Exploring readiness for language learning autonomy among distance learners in Sabah, Malaysia - Junaidah Januin (The Asian Society of Open and Distance Education, Japan, 2007)
Distance learners have a wide variety of reasons for pursuing learning at a distance ; constraints of time, distance, and finances, the opportunity to take courses or hear outside speakers who would otherwise be unavailable, and the ability to come into contact with other students from different social, cultural, economic, and experiential backgrounds. As a result, they gain not only new knowledge but also new social skills, including the ability to communicate and collaborate with widely dispersed colleagues and peers whom they may have never seen. The term ‘distance learner’ itself invites an assumption that a learner of this type is expected to have gained, to some extent, learner autonomy. In Malaysia, the notion of language learning autonomy may be alien to many learners of English-as-a-Second-Language, especially Malay students, since the pedagogical traditions in Malaysia are usually teacher-centred in nature. Moving from teacher-centred to learner-centred through language learning autonomy may do wonders to promote learning among Malay students. This paper investigated the readiness for language learning autonomy of the distance learners in one higher learning institution in Sabah, Malaysia. The degree of their readiness for language learning autonomy was examined through a set of three questionnaires, designed to investigate each learner’s perceptions and beliefs in the three areas of perceptions on the teachers’ roles, the learner’s reliance on the teachers, and the learner’s confidence or beliefs in his / her own language learning abilities. This study explored how the data derived from the questionnaires revealed the status of readiness of the learners for language learning autonomy.